2008
DOI: 10.1158/0008-5472.can-07-2931
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Pathogenesis-Related Protein 1 Exerts Tumor Suppressor Activities through Proapoptotic Reactive Oxygen Species–c-Jun–NH2 Kinase Signaling

Abstract: Glioma pathogenesis-related protein 1 (GLIPR1), a novel p53 target gene, is down-regulated by methylation in prostate cancer and has p53-dependent and -independent proapoptotic activities in tumor cells. These properties suggest an important tumor suppressor role for GLIPR1, yet direct genetic evidence of a tumor suppressor function for GLIPR1 is lacking and the molecular mechanism(s), through which GLIPR1 exerts its tumor suppressor functions, has not been shown. Here, we report that the expression of GLIPR1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 50 publications
8
71
1
4
Order By: Relevance
“…11 A deficiency in TAP has been linked to several cancers, including breast and prostate cancer. 11,23,27 We previously found that the expression of TAP is significantly downregulated in prostate cancer, which is associated with tumor cell proliferation, as well as with an increased risk of cancer recurrence. 23,24 Overexpression of TAP inhibits prostate cancer growth in the absence of vitamin E both in vitro and in vivo through suppression of the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…11 A deficiency in TAP has been linked to several cancers, including breast and prostate cancer. 11,23,27 We previously found that the expression of TAP is significantly downregulated in prostate cancer, which is associated with tumor cell proliferation, as well as with an increased risk of cancer recurrence. 23,24 Overexpression of TAP inhibits prostate cancer growth in the absence of vitamin E both in vitro and in vivo through suppression of the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MEKK2 is involved in JNK and ERK5 activation, and JNK activation can promote apoptosis in GBM cells (12,19).…”
Section: Mir-26a Inhibits Map3k2/mekk2 Expression and Jnk-dependentmentioning
confidence: 99%
“…We also identified MAP3K2/MEKK2, an activator of the JNK pathway, which has been implicated in apoptosis and tumor suppression (13,19). Thus, PTEN, RB1, and MAP3K2/MEKK2 were chosen for further study.…”
mentioning
confidence: 99%
“…Overexpression of GLIPR1 in cancer cells leads to suppression of colony growth and induction of apoptosis. Mechanistic analysis indicates that GLIPR1 up-regulation increases the production of ROS, leading to apoptosis through activation of the JNK signaling cascade [56] . However, in p38-related apoptosis that is independent of ROS generation, JNK seems to execute a reverse function.…”
Section: Ros Involve Apoptosis That Relates To the P38 Pathwaymentioning
confidence: 99%